The Correlation between Hypogonadism and Coronary Heart Disease in Men at RSUP Prof. Ngoerah - Liu, Jovita Theodora; I Gusti Ngurah Pramesemara; I Made Putra Swi Antara; Ida Ayu Dewi Wiryanthini (Universitas Airlangga, 2024)
Hypogonadism is a clinical syndrome associated with aging, characterized by low levels of testosterone in a man's body. Hypogonadism can lead to various diseases, one of which is coronary heart disease. Coronary heart disease is a cardiovascular disease caused by the buildup of plaque in the coronary arteries. This research aims to examine the relationship between hypogonadism and coronary heart disease in men at RSUP Prof. Ngoerah. The research was conducted analytically with a case-control design. Hypogonadism was measured using the ADAM score questionnaire, which consists of 10 questions. The research sample comprised men who were coronary heart disease patients and men who were non-coronary heart disease patients aged 35–45 years in the Gedung Pelayanan Jantung Terpadu RSUP Prof. Ngoerah. The sample was determined using a consecutive sampling technique, with a total of 50 participants. The research results found that 28 participants (56%) tested positive for hypogonadism, and 22 participants (44%) tested negative for hypogonadism. A p-value of 0.004 indicated a significant relationship (p ≤ 0.05) between hypogonadism and coronary heart disease. The calculated Odds Ratio (OR 95% CI) between hypogonadism and coronary heart disease was 5.6 (1.648 – 19.232). Among the research participants, 19 (76%) were both positive for hypogonadism and coronary heart disease. Meanwhile, 16 participants (64%) were negative for both hypogonadism and coronary heart disease. The lower the testosterone levels in men, the higher the risk of developing coronary heart disease. Coronary heart disease patients with hypogonadism were 5.6 times more likely to have the condition compared to those without hypogonadism. There is a significant correlation between andropause and coronary heart disease in men at RSUP Prof. Ngoerah.